Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Effect of water level fluctuation on the plants of the littoral zone - Vörös, Lajos; Kravinszkaja, Gabriella; Présing, Mátyás; V.-Balogh, Katalin; Tóth, Viktor (Acta Scientiarum Socialium, 2013)
Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Effect of water level fluctuation on the plants of the littoral zone While the Hungarian public was primarily concerned with the water quality of Lake Balaton in the 1980s and 1990s, low water levels and their environmental effects became the focus of public attention in 2002, 2003 as well as 2012. Accurate and reliable monthly and yearly data about the water balance of Lake Balaton has been available since 1921. The amounts of water getting into the lake from the catchment area have been considerably less than average in nine percent of the period between 2001 and 2012; the water in the catchment area became scarce and the water levels of the lake notably decreased during the drier than average years of 2001-2004 and 2012. Cladophora glomerata (filamentous green alga) appeared in large quantities in the shallow waters of the south shore in the summer of 2002, 2003 as well as 2012. It is not a new phenomenon: the first documented Cladophora explosion in Lake Balaton was in 1934. Scientists at the Balaton Limnological Institute (Center for Ecological Research of the Hungarian Academy of Sciences) studied the Cladophora vegetation of the south shore in July 2003. They found that excessive Cladophora growthâ€”harming tourism with its gooey green mats and rotting muckâ€”appeared where the water depth was lower than 30 cm. This explosion, however, is not a consequence of water pollution but an unavoidable consequence of the low water levels. The results show that the photosynthetical apparatus of the main submerged macrophyte species have adapted to the semi-dark waters of Lake Balaton. The photosynthetical parameters of submerged macrophytes indicate that they can survive and disperse in parts of the lake where the water is no deeper than 2.2-2.3 m. It means that the area suitable for the establishment of submerged macrophytes increases by 60 percent with a 50 cm decrease in the water levels, while a 100 cm decrease means a threefold increase in the size of the area favourable for submerged macrophytes. The decrease in water levels contribute considerably to the spread of reed. This is due the increase in drier areas suitable for sexual reproduction on the one hand and to the oxidation of sediment on the other. The emerging of a reed-covered area out of the waterâ€”even if for a short periodâ€”contributes considerably to the prevention of reed decline. The artificial stabilization of the water levels in the past fifty years has greatly contributed to the slow degradation of the flora in the littoral zone. At the same time, the low water levels of the past decade have shown that low water levels do not damage the macrophyte populations of Lake Balaton.